2018
DOI: 10.1177/0300060517740813
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between antimicrobial-resistance programs and antibiotic dispensing for upper respiratory tract infection: An analysis of Australian data between 2004 and 2015

Abstract: ObjectiveNPS MedicineWise aims to ensure that medicines are prescribed and used in a manner consistent with current evidence-based best practice. A series of nationwide educational and advertising interventions for general practitioners and consumers were implemented in Australia between 2009 and 2015 with the aim of reducing antibiotic prescriptions for upper respiratory tract infections (URTIs). The work described in this paper quantifies the change in antibiotic dispensing following these interventions.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…[6] Several studies have reported the relationship between the uncontrolled use of antibiotics and increased resistance to them. [7] Countries having the highest rate of antibiotic use have reported highest antibiotic resistance. [8] While health-care physicians are aware of the fact that most of the URTIs have viral origin, [9] prescription of antibiotic for URTIs has become a common practice in pediatric clinics.…”
Section: Research Articlementioning
confidence: 99%
“…[6] Several studies have reported the relationship between the uncontrolled use of antibiotics and increased resistance to them. [7] Countries having the highest rate of antibiotic use have reported highest antibiotic resistance. [8] While health-care physicians are aware of the fact that most of the URTIs have viral origin, [9] prescription of antibiotic for URTIs has become a common practice in pediatric clinics.…”
Section: Research Articlementioning
confidence: 99%
“…Interventions designed to improve antimicrobial prescribing have shown success amongst GP trainees and supervisors [18][19][20][21][22]. Additionally, international interventions focussing on factors influencing inappropriate prescribing have been shown to improve antibiotic prescribing over time [15,[23][24][25][26], particularly for respiratory tract infections [27][28][29][30]. These interventions include educational sessions [31,32] and support material for GPs [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that each year infections caused by antibiotic-resistant pathogens result in 700,000 deaths worldwide; the number might reach 10 million in 2050 if there is no effective action to curb resistance [1]. The overuse of antibiotics is considered as an important contributor to antibiotic resistance, [2] which could be effectively reduced by appropriate antibiotic stewardship [3]. To guide the use of antibiotics, the World Health Organization (WHO) proposed a three-category antibiotic classification system in 2017 [4]: namely access, watch, and reserve group antibiotics.…”
Section: Introductionmentioning
confidence: 99%